Primary Care and Linked Secondary Care Encounters for Foot and Ankle Problems in Children and Young People: A Population‐Based Cohort Study in England - Emma Rezel‐Potts; Catherine Bowen; Kate M. Dunn; Christopher I. Jones; Martin C. Gulliford; Stewart C. Morrison (Journal of Foot and Ankle Research, 2025)
ABSTRACT Background In the United Kingdom, foot and ankle problems in children and young people are typically seen by the general practitioner in primary care and referred to secondary care or community services for specialist assessment and intervention. Following initial presentation to primary care, we have described the secondary care services accessed by children and young people with foot and ankle problems. We have also explored the sociodemographic variables associated with referrals to secondary care. Method This was a population‐based cohort study using the UK Clinical Practice Research Datalink (CPRD) Aurum primary care database and linked Hospital Episode Statistics (HES) Outpatient database. We extracted data for all children and young people up to 18 years of age with a consultation for a foot and ankle problem from 1st January 2015 to 31st December 2021 (CPRD) and included those with linked data in secondary care (HES database) in our analyses. Results 346,454 children and young people aged 0–18 years were identified in CPRD and eligible for linkage; 5030 had at least one referral within 18 weeks. The most common reason for referral was musculoskeletal or unspecified pain and 2935 had a referral to trauma and orthopaedics, 1314 for paediatric services, 678 for physiotherapy and 274 for diagnostic imaging. Odds for referrals were higher among younger age groups (odds ratio (OR) 1.29 and 95% confidence interval (CI) 1.25–1.33). Those in other (OR 0.77 and 95%CI 0.72–0.82), Asian (OR 0.81 and 95%CI 0.77–0.86) and Black (OR 0.85 and 95%CI 0.8–0.91) ethnic groups had lower odds of referral compared to those in the White group. Conclusion These findings represent the first analyses of secondary care referrals for children and young people with foot and ankle problems. We have identified that musculoskeletal symptoms were most common reason for referral and the most common speciality involved in assessing foot and ankle problems was trauma and orthopaedics. We have reported sociodemographic differences in secondary care referrals and these findings could be indicative of inequalities in access to care and should be a priority for further research.